Indústria têxtil no nordeste: a experiência de Alagoas e Sergipe - Silva, Bruno Bianchi Gonçalves da (2019)
It deals with the evolution of the textile industry in the states of Alagoas and Sergipe, highlighting its dissensions in recent decades, tied to the influences of the sectoral movement at various scales (regional, national and global). The research is anchored in the theoretical reference of Milton Santos with the socio-spatial formation, Ignacio Rangel through the dualities of the brazilian economy and in the geographical combinations of André Cholley present in the course of the three chapters. The textile trajectory in these states is in line with the sectoral-regional framework until the 1950s, marked by the regional monopolies of the textile factories, taking advantage of the low commercial integration of the Brazilian territory. The 1950s saw the decline of some traditional factories, while the states of Pernambuco and Ceará made better use of the interregional displacement of production units under the inauguration of the regional incentives promoted by Sudene. Finally, with the most recent textile production displacement, with a greater influence in the world, due to the commercial opening in the 1990s, Alagoas and Sergipe, with similar trajectories in the sector, differences became evident from the 2000s. When Sergipe took advantage of the existence of a textile park that has managed to cross successive crises attracts new productive units of the South and Southeast. It is emphasized in the course of the research that the displacement of production occurred only in the most labor-intensive production stages. The strategies of production displacement of textile companies were marked not only by external factors, but also by internal factors, such as the change of the national cotton production center in the 1990s, differences in the cost of labor, the consumer market and favorable geographical location.